TINJAUAN PEMBEBANAN PADA STRUKTUR ATAS DERMAGA KAPASITAS 10000 DWT DI TELUK TOMORI - Ashari Ibrahim; Andi Maal (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research is based on the scenario of a port construction with a capacity of 10,000 DWT to serve the type of tanker ship carrying liquid bulk cargo. The port plan does not require a large loading and unloading area, the pier is planned to be 15 m length and 4.5 m width, with separate fender and bollard construction. The pier construction is connected by a trestle construction with 166 m length and 3.5 m width. The loading scenario consists of dead load (DL), live load (LL), wave load (G), current load (A), earthquake load (E), mooring load (M), and berthing load (B) which are modeled in combination loading. Structural analysis was carried out by modeling using ETABS software for pier and trestle construction. The safety review in this study focused on assessing the PMM ratio of piles. Based on the results of modeling using ETABS, the PMM Ratio value for piles on piers ranges from 0.17 to 0.23, while on trestle it ranges from 0.23 to 0.30. The PMM Ratio value is less than one, which means the construction is quite safe based on the combination of working loads.